Natural outbreak of Newcastle disease in village chickens obtained from various sources in semi-arid region of Nigeria - Abubakar, Mustapha B.; Ani, Monday; El-Yuguda, A. D.; Baba, S. S.; Gambo, H. I.; Geidam, Y. A.; Shettim, Y. M.; Zannah, Y. M.; Abu, Jalila; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
An outbreak of Newcastle Diseases (ND) was investigated in caged local chickens that were obtained from various locations in and around Bama, Nigeria. A morbidity rate of 58% and morality rate of 60% were recorded among the affected birds. The birds started dying two days after the onset of clinical signs. The signs observed were consistent with ND and included respiratory distress with gasping and sometimes coughing; nervous signs such as paralysis, torticollis; loss of appetite, swollen head and wattles, sometimes ocular and nasal discharge, severe conjunctives and death after some days. The death peaked on day 5 following onset of clinical signs and ceased on day 13 after the onset. The histopathological lesions observed include congestion of the spleen, kidney and lungs, hemorrhages in the proventriculus and kidney. Majority 20/26 (76.9%) of the sera tested during the acute phase of the disease were negative of ND antibodies while those collected during the convalescent phase of the disease showed varying titres ranging between 1:20 and 1:80, suggested of a recent viral infection. All tissue samples collected from infected birds were positive for Newcastle disease virus haemagglutinating antigens and titers ranging between 1:2 and 1:6 were recorded. It was concluded that the outbreak might have been as a result of introduction of some in apparently infected chicken into the cage. It was recommended that the birds should be screened for the presence of ND virus before introduce into a new flock in addition village chicken should be obtained from source that are not infected with the virus and village chicken should be vaccinated routinely against ND.